Pengaruh Kepuasan Kerja dan Komitmen Organisasi Terhadap Turnover Intention Karyawan pada PT Gemilang Tunas OtomotifThe Effect of Job Satisfaction and Organizational Commitment on Employee Turnover Intention at PT Gemilang Tunas Otomotif: The Effect of Job Satisfaction and Organizational Commitment on Employee Turnover Intention at PT Gemilang Tunas Otomotif - Hagna Mustopa (Jurnal Mnajemen | Ekonomi | Akuntansi, 2024)
Job satisfaction is basically a person who carries out his work wants to feel secure and have great loyalty to the industry. Not only job satisfaction, there are other matters that are the attitude of employees who want to have a positive impact on the company is a commitment. Explaining that employees who have a large level of commitment tend to be more attached to the organization and less likely to move. This study aims to analyze the influence of job satisfaction and organizational commitment on employee Turnover Intention at PT Gemilang Tunas Otomotif. The research procedure used is quantitative with a method of collecting information through a questionnaire distributed to 50 employees of PT Gemilang Tunas Otomotif. The results of this research prove that job satisfaction partially does not affect employee Turnover Intention as seen from the value of t-calculating( 2. 047) t- table ( 2. 011) with a Sig value of 0. 046< 0. 05. If the organization's commitment is partial, the organization's commitment has a positive and significant effect on employee Turnover Intention by displaying that the value of t- calculate( 3. 225) t- table ( 2. 011) with a value of Sig. 0. 002< 0. 05. There is a significant and negative influence between job satisfaction and organizational commitment to employee Turnover Intention. That is, continuing to have a high level of job satisfaction and organizational commitment of employees, continuing to have a low level of employee Turnover Intention. This shows that job satisfaction and organizational commitment are significant aspects that can affect employee Turnover Intention.Job Satisfaction, Commitment, Turnover Intention